2021
DOI: 10.18326/attarbiyah.v6i1.15-29
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception on Islamic education toward e-learning classes during covid-19 pandemic

Abstract: The aim of this research is to find out the students’ perception of Islamic education course conducted online learning during a pandemic outbreak. This impact affects the learning process. The researchers used a qualitative research approach with a survey method and the data collection were gained through a questionnaire and interview which were conducted online. The participants in this study were 115 students from the even semester and of English Education Program in English for Islamic studies course from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Other than the problems mentioned previously, the availability of LMS or online learning platforms seems crucial in modern education. While on the other hand, students prefer simpler platform, such as WhatsApp [18], [19]. Even though this phenomenon creates gap in implementing online learning in higher education, the quality of education remains the top priority.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the problems mentioned previously, the availability of LMS or online learning platforms seems crucial in modern education. While on the other hand, students prefer simpler platform, such as WhatsApp [18], [19]. Even though this phenomenon creates gap in implementing online learning in higher education, the quality of education remains the top priority.…”
Section: Introductionmentioning
confidence: 99%
“…Lubis and Khairuna (2019) observed that the coexistence of scientific and non-science issues is one potential notion of an integrated approach and that many researchers have proved the relevance of religion (Lubis & Khairuna, 2019). Religion governs all elements of its adherents' lives as people, members of society, and members of their environment (Djamdjuri & Maeleni, 2021). Moreover, the National education goal in the essence is to build Indonesian people completely and religious education is one of the activities to build a strong mental and spiritual foundation (Mujahidin, 2017).…”
Section: A Introductionmentioning
confidence: 99%